On the Interaction Between Human Plasma Kallikrein and C1-Esterase Inhibitor - Nilsson, Torbjörn (Thrombosis and Haemostasis, 1983)
The kinetics of the reaction between human plasma kallikrein and CĪ-esterase inhibitor was studied in a purified system. By monitoring the inhibition reaction for extended periods of time, it was found to proceed in two consecutive steps, a fast reversible second-order binding step followed by a slower, irreversible first-order transition. The rate constants in this reaction model were determined, as well as the dissociation constant of the initial, reversible enzyme-inhibitor complex. Thus, at 37° C the second-order rate constant was found to be 5 · 104 M -1 · s-1, the first order rate constant was 5 · 10-4 s-1 and the dissociation constant K was 1.5 · 10-8 M. Heparin (28 U/ml) and 6-aminohexanoic acid (10 mM) had no effect on the k1 of the of the reaction.
Keywords: CĪ-esterase inhibitor; Kallikrein; Kinetic mechanism